Tracer tests as a tool for planning the monitoring of negative impacts of the Mozelj landfill (SE Slovenia) on karst waters - Kogovšek, Janja; Petrič, Metka (Acta Carsologica, 2010)
<span style="color: black; line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 9pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Minion Pro"; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Tracer tests are one of the most useful researchmethods in karst hydrogeology and they have proved a valuable tool in various applied projects. In recent years we carried out a series of tracer tests, and their results were used as the bases for planning the monitoring of water quality in the influence areas of various pollution sources. In this paper, a case study of tracing at the landfill near Mozelj in southeastern Slovenia is described. The first goal was testing of the functioning of three monitoring boreholes, whichwere drilled at the margins of the landfill. As often happens in heterogeneous karst systems, they did not intersect the main flow paths from the landfill and are not suitable as monitoring points. On the other hand, the findings about the characteristics of tracer transport in the karst system and outflow throughthe karst springs were used for identifying the most suitable springs for monitoring and preparing an adequate sampling plan, whichshould be adapted to hydrological conditions.